Lipid Profile Disturbance in Acne Vulgaris of Iraqi patients - Ayat A. Hamood; Hind M Mousa (University of Thi-Qar Journal of Science, 2022)
Acne vulgaris wide speared skin disease that cause psychological impact with increased risk of depression.This research on 90cases from male and female, 45 of acne patient and 45 of healthy controls. A blood samples was collected in addition to some information from all cases. Lipid profile was estimate. The results found that females patients more than males, and most of the acne patients resided in urban areas . Also, acne patients had significantly increased levels of cholesterol, triglycerides (TG), high-density lipoprotein (HDL) and low-density lipoprotein (VLDL) in their blood. On the other hand, a significant decrease in the level of low-density lipoprotein (LDL) . It had concluded that the difference in serum lipid levels between acne patients and healthy individuals, indicates that alteration of lipid profile is an significant factor in development acne in Iraqi patients